The Influence of Classroom Management toward Students’ English Achievement at SMU Muhammadiyah Salatiga (A Case Study of Second Year Students of SMU Muhammadiyah Salatiga in the Academic Year of 2004/2005) - Triyono Triyono (UIN Salatiga, 2009)
This research aims to find out the influence of classroom management toward students’ achievement in English. The research was conducted at SMU Muhammadiyah Salatiga, Central Java, Indonesia. The writer focuses on the second year students in the academic year of 2004/2005. It is a Quantitative Research. Questionnaire and direct observation are the instruments used to take the data. The score of classroom management of SMU Muhammadiyah Salatiga is 87.6%, fairly high. While the score level of the second year students of SMU Muhammadiyah Salatiga is 72%. This score level is satisfactory category of achievement level of most students. It means that better classroom management influences better English achievement.Keywords:Classroom Management; Achievement; SMU Muhammadiyah